Asylum [a novel] - McGrath, Patrick 1950- (Random House, 1997)
A woman whose husband is a doctor working in an asylum has an affair with a patient, a sculptor who killed his wife from jealousy. When he escapes she follows him, but his jealous fits send her back to her husband. The sculptor is caught, the doctor changes jobs, but that is not the end of the story. One day she will rejoin the sculptor, this time as a fellow-patient.